TUMOR SUPRESOR GEN p53 SEBAGAI TARGET PENGOBATAN “CANCER” - Jekson Martiar Siahaan; Tengku Muhammad Fauzi (Majalah Ilmiah METHODA, 2021)
The p53 protein functions as a biological molecule that breaks the cycle of damage to DNA damage, even the important function of this molecule is to check whether the organ cells are complete or damaged. However, p53 can undergo mutations that will instead be an oncogene. One way to deal with this is gene therapy, namely PRIMA-1 (p53 Reactivation and Induction of Massive Apoptosis). Until now, further studies are still needed on the effectiveness of this therapy